PENERAPAN MODEL INKUIRIUNTUK MENINGKATKAN HASIL BELAJAR PADA POKOK BAHASAN GERAK - Wirawan, Eztra; Sitompul, Stepanus Sahala; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to improve student learning outcomes by applying the science-physics inquiry learning model on the subject of motion. The form of this research was Classroom Action Research (CAR) which was carried out in 2 cycles with stages of planning, action, observation and reflection. Subjects in this study were students of class VII H Pontianak 23 Public Middle School consisting of 30 students. Data collection through tests, observation sheets and documentation. The results showed the average post-test value of cycle I was 76 and cycle II was 87. The completeness of learning outcomes in cycle I was 50% while in cycle II was 86.7% meaning that there was an increase in learning outcomes by 36.7% of the cycle I to cycle II. As for the results of observations made, obtained data is that after the inquiry learning model is applied the learning process becomes more active. The results of this study indicate that the application of inquiry learning models on the subject of motion can improve student learning outcomes. This research is expected to be used as an alternative teacher to improve science-physics learning outcomes in the subject of motion.Â Keywords: learning outcomes, application of inquiry learning models, research subjects discussion of motion